IMPROVING STUDENTS’ ABILITY IN WRITING ANNOUNCEMENT THROUGH GALLERY WALK TECHNIQUE AT THE TENTH GRADE OF SMA NEGERI 1 GUNUNGSITOLI IDANOI IN 2022/2023 - Larosa, Agus Kriswinar; Harefa, Afore Tahir; Harefa, Trisman (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research was aimed to improve the students’ ability in writing announcement through Gallery Walk Technique at tenth grade of SMA Negeri 1 Gunungsitoli Idanoi in 2022/2023. The researcher employed a classroom action research design conducted over two cycles. The research focused on the students of X-MIPA. The instruments utilized for this study were a writing test, and an observation sheet. The results of each cycle revealed that in Cycle I, the technique was not successful. Therefore, the research continued to the next cycle after revising the plan based on the weaknesses identified in Cycle I. The findings of Cycle II indicated that 7 students (33%) reached the 'good' level, while 14 students (67%) achieved the 'very good' level. These results demonstrate that the implementation of the 'Gallery Walk Technique' in this study successfully enhanced students’ writing announcement text.